2010
DOI: 10.1128/jvi.01219-10
|View full text |Cite
|
Sign up to set email alerts
|

Proteasome InhibitionIn VivoPromotes Survival in a Lethal Murine Model of Severe Acute Respiratory Syndrome

Abstract: Ubiquitination is a critical regulator of the host immune response to viral infection, and many viruses, including coronaviruses, encode proteins that target the ubiquitination system. To explore the link between coronavirus infection and the ubiquitin system, we asked whether protein degradation by the 26S proteasome plays a role in severe coronavirus infections using a murine model of SARS-like pneumonitis induced by murine hepatitis virus strain 1 (MHV-1). In vitro, the pretreatment of peritoneal macrophage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
37
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(43 citation statements)
references
References 51 publications
5
37
1
Order By: Relevance
“…MG-132 administered in relatively large doses (4 mg/kg, repeated seven times) did not ameliorate tubulointerstitial fibrosis in rat unilateral ureteral obstruction [37]. Positive effects of MG-132, namely attenuation pneumonitis and cytokine gene expression in vivo by reducing coronavirus were observed [28].…”
Section: Systemic Administration Of Proteasome Inhibitionmentioning
confidence: 93%
See 2 more Smart Citations
“…MG-132 administered in relatively large doses (4 mg/kg, repeated seven times) did not ameliorate tubulointerstitial fibrosis in rat unilateral ureteral obstruction [37]. Positive effects of MG-132, namely attenuation pneumonitis and cytokine gene expression in vivo by reducing coronavirus were observed [28].…”
Section: Systemic Administration Of Proteasome Inhibitionmentioning
confidence: 93%
“…In a low dose (0.1 mg/kg) MG-132 administered intraperitoneally once per day even for 2 or 8 weeks may effectively prevent cardiac remodelling and dysfunction in pressure-overloaded hearts without marked drug toxicity [29]. The effects of intraperitoneal injection of MG-132 was also studied on urinary [37], musculoskeletal [20,42], and respiratory systems [28]. The study revealed that MG-132 is not an adequate treatment to prevent endotoxin-induced diaphragmatic dysfunction [20,42] but partially prevents muscle atrophy associated with disuse [20].…”
Section: Systemic Administration Of Proteasome Inhibitionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, it is feasible that this type of immune response contributes to the initiation of epithelial dysfunction and repeated airway damage in virus-mediated exacerbations in asthma. As inhibition of the proteasome has been shown not only to attenuate virus replication in acute lung pneumonitis but also to affect antigenic peptide processing and subsequent cytotoxic T-cell-mediated lysis responses, this may add to the therapeutic potential of proteasome inhibitors in asthma [70,71]. Only recently, the rationale for therapeutic application of proteasome inhibitors in asthma has been extended to the idea of depleting immunoglobulin-secreting plasma cells.…”
Section: Asthmamentioning
confidence: 99%
“…Cyclosporine and FK506 have emerged as examples of such inhibitors (De Wilde et al, 2011;Pfefferle et al, 2011;CarbajoLozoya et al, 2012). Other host pathway proteinsthat are potential antiviral drug targets have been identified (Ma et al, 2010;Bhardwaj et al, 2012;Millet et al, 2012;Smith et al, 2012;Zhao et al, 2012).…”
Section: Host Pathway Inhibitorsmentioning
confidence: 99%